A practical grid generation procedure for the design of free-form structures. (February 2018) - Gao, Boqing; Li, Tierui; Ma, Teng; Ye, Jun; Becque, Jurgen; Hajirasouliha, Iman
Highlights: A practical framework is presented to automatically generate grid for free-form structural design. Grids are generated with limited number of predefined guide lines. Pre-selected guide lines determines the fluency of generated grids. Software developed using C++ resulted in rapid grid generation and regular mesh. Software provides essential visualization and data exchange functions. Abstract: Computer aided design software enables the rapid conceptual creation of a curved surface geometry, whereas it is neither a convenient nor an obvious task for engineers to create a discrete grid structure on a complex surface that meets architectural and aesthetic requirements. This emphasizes the importance of grid generating tools and methods in the initial design stage. This paper presents an efficient design tool for the synthesis of free-form grid structures based on the "guide line" method, employing a fast and straightforward approach which achieves grids with rods of balanced length and fluent lines. The process starts with defining a limited number of curves (named the "guide lines") on the surface, which are then used to determine the directions of the 'rods' of the grid. Two variations of this concept are introduced in this paper: the 'Guide Line Scaling Method' (GSM) and the 'Two Guide Lines with Two End Vertices Method' (2G2VM). Case studies are provided which illustrate the successful execution of these procedures. The results show that the free-form grid structures generated with the proposed methods feature a regular shape and fluent lines, thereby satisfying aesthetic requirements. These two methods have been programmed into the software ZD-Mesher, enabling rapid grid generation for structural design purposes.